Food Freezing Today and Tomorrow - Bald, W. B. (New York : Springer, 1991)
Food Freezing: Today and Tomorrow represents the contributions of the invited speakers to an advanced study seminar held by the Institute for Applied Biology of the University of York during April 1990. The main objective of the seminar was to bring together food scientists and engineers to discuss their mutual problems and to seek new directions for possible solutions.
Keywords: Life sciences; Biochemistry; Life Sciences; Biochemistry, general